Analyzing Sustainability Communication through the Life Cycle Assessment Approach: A Conceptual Examination of Apple’s Carbon-Neutral Watch Campaign - Eşidir, Osman Vedüd; Bak, Gökhan; Bak, Alparslan (My University, 2025)
This study aims to analyze Apple’s 2023 carbon-neutral Apple Watch campaign from the perspective of Life Cycle Assessment (LCA) within communication processes. The research argues, within a conceptual framework, that sustainability-oriented advertising cannot be reduced to short-term message delivery, but should instead be understood as producing measurable environmental and social impacts throughout the entire life cycle. Although the LCA methodology was originally developed to evaluate the environmental impacts of products and services, this study adapts and applies it to communication practices. Moreover, since the LCA approach is also widely applied in fields such as agricultural economics and natural resource management, it adds an interdisciplinary dimension to the methodological framework of this research. In this context, the analysis focuses on how claims of carbon neutrality were articulated during the production, use, and disposal phases, how the emphasis on renewable energy and recycled materials was communicated, and how these strategies were reflected in both social perception and brand image. The study does not rely on surveys or field research; rather, it is based on secondary data obtained from publicly available corporate reports, legal documents, and media sources. The findings reveal that the campaign established a sustainability-oriented communication strategy; however, its reliance on carbon credits and ongoing legal processes has limited the perceived credibility of its messages. This highlights the necessity for sustainability communication to be conducted within the principles of verifiable data and transparency. By demonstrating the applicability of the LCA methodology to communication research, the study contributes to the literature both theoretically and methodologically, while also proposing a new conceptual framework for researchers seeking to evaluate the long-term impacts of sustainability-oriented advertising campaigns.
Keywords: Sustainability Communication; Carbon Neutrality; Life Cycle Assessment (LCA); Advertising Compaigns; Apple Watch